MODEL KESIAPSIAGAAN MENGHADAPI BENCANA GEMPA BUMI BERBASIS SEKOLAH DI KECAMATAN LEMBANG KABUPATEN BANDUNG BARAT - Romadona, Dede (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted on the Maribaya Timur school community in Lembang Subdistrict, West Bandung Regency, which is an active community in the area that is threatened by the potential for earthquake disasters due to the active Lembang fault. Disaster risk reduction efforts are pursued through increasing school-based preparedness that involves members of the school community, surrounding communities and various institutions that are associated with reducing the risk of school-based earthquake. Increasing preparedness against earthquakes focuses more on aspects of capacity building of school communities in reducing disaster risk, while aspects of vulnerability and threats have not been the focus of disaster risk reduction. The steps taken refer to the element of preparedness by aligning with the conditions, needs and potential that exist in the school community. Theoretically, if the school community has preparedness to face an earthquake disaster, the risk of earthquake disaster in the school community will be reduced so that it can minimize losses, victims and suffering that will be caused by the earthquake disaster.